PENGEMBANGAN LKS TEMATIK-INTEGRATIF BERBASIS KARAKTER PADA PESERTA DIDIK KELAS IV SDN SRIKAYANGAN - Veryliana Purnamasari (Universitas PGRI Semarang, 2015)
This study aims to: (1) develop a thematic student activity sheet on the theme ?óÔé¼?ôWhere I Live?óÔé¼?Ø suitable for fourth grade students of Public Elementary School 2 Tinggarjaya, and (2) determine the effectiveness of thematic-integrative student activity sheet grade students Public Elementary School Srikayangan developed. This study refers to the development and research developed by Borg & Gall that includes. Subject research fourth grade students of SDN Srikayangan. Collecting data used interview guides, product assessment student activity sheet, teacher observation sheets, observation sheets of learners, the teacher questionnaire responses and questionnaire responses of learners. Mechanical analysis using quantitative descriptive analysis techniques. Data enhancement honest and caring character were analyzed using gain standard. Data honest and caring character differences were analyzed using t test with a significance level of 5%. The results show that the material student activity sheet according to experts, evaluation, curriculum and teachers in terms of aspects of integrating character got good score of 4 categories, aspects of Pedagogy got a very good score of 4.46 category, construction got a score of 4.49 excellent and the technical category got a score of 4, 32 categories very well developed so student activity sheet fit for use. In the field tests it is obtained a significance value gain honest and caring character as much as 0.000 <0.05, so H0 is rejected. This shows that there are significant differences on average increase of the character honest and caring